Discharge Communication of Dementia-Related Neuropsychiatric Symptoms and Care Management Strategies During Hospital to Skilled Nursing Facility Transitions. (September 2021) - Gilmore-Bykovskyi, Andrea L.; Hovanes, Melissa; Mirr, Jacquelyn; Block, Laura
Provided the complexity of managing dementia-related neuropsychiatric symptoms (NPS), accurate communication about these symptoms at hospital discharge is critical to facilitating safe and effective transitions, particularly transitions from hospitals to skilled nursing facilities (SNF), which are often poorly managed. Skilled nursing facilities providers have cited undercommunication regarding NPS as a major challenge that contributes to poor outcomes including rehospitalization. This multisite retrospective cohort study identified omission rates for NPS and associated management strategies in discharge communication as compared to medical record documentation in the 72 hours preceding discharge among hospitalized patients with dementia. High rates of omission were found across NPS and management strategies: anxiety (94%), agitation/aggression (77%), hallucinations (85%), 1:1 supervision (90%), high fall risk (89%), use of restraints (91%). Omission rate for new or modified antipsychotic medication was 12.9%. Findings underscore the need for additional research on cross-setting communication regarding care needs of patients with dementia—who often cannot communicate these needs on their own—in facilitating high-quality transitions.